Studi Komunitas Zooplankton Sebagai Gambaran Kualitas Perairan di Teluk Palu Sulawesi Tengah - Elijonnahdi Elijonnahdi; Miswan Miswan; Ririn Prawita (Biocelebes, 2012)
Research of the "Study Zooplankton Community As Overview Water Quality of Central Sulawesi in Palu Bay" was conducted from March to May 2012. This research was aimed to Determine the structure of zooplankton community in waters bay of Palu. Samples were taken vertically and horizontally by using a plankton net and Lamotte water sampling at four research stations, they are: Station 1 in the area of the river mouth of Palu, station 2 in the area of Tondo village settlements, station 3 in the areas of sand mining and quarrying C Taipa, and station 4 in the area of PLTU. Samples were observed and analyzed in the laboratory of the Department of Environmental Biology Faculty of Mathematics and Natural Sciences. The results showed that in the bay Palu found three phyla, 3 classes, 7 orders of zooplankton are classified into 30 types. The results of the analysis of the diversity index (H ') ranged from 0.69 to 2.61 belong to the diversity of medium and low. Uniformity index (E) ranged from 0.60 to 1.00, belonging to the high uniformity. Total abundance at the surface ranged from 0.12 to 3.60 ind / l. Total abundance at depths ranging from 30-490 ind / l. Key words: Community, zooplankton, water quality, the bay of Palu